Reformed public theology: a global vision for life in the world - Kaemingk, Matthew (Baker Academic, a division of Baker Publishing Group, 2021)
Introduction: Toward a Reformed public theology / Matthew Kaemingk -- Immigrants, refugees, and asylum seekers : the migratory beginnings of Reformed public theology / Rubén Rosario Rodríguez -- Let every tongue confess : language diversity and Reformed public theology / James Eglinton -- African decolonization and Reformed theology / Nico Vorster -- The Dutch and death : pastoral observations and theological reflections / Margriet van der Kooi and Cornelis van der Kooi -- Religious pluralism in Indonesia : reformed reflections / N. Gray Sutanto -- A Reformed theology of work in New York / Katherine Leary Alsdorf -- Political economy in Brazil : a Reformed response / Lucas G. Freire -- Workers' rights in China : a Reformed case for labor unions / Agnes Chiu -- Modern political ideologies : a Reformed alternative / Bruce Riley Ashford and Dennis Greeson -- Power politics in the Philippines : a Reformed response to the populism and violence of Duterte / Romel Regalado Bagares -- Reflections from a Reformed activist / Stephanie Summers -- Japanese aesthetics and Reformed theology : reflections on Rikyū, Kintsugi, and Endō / Makoto Fujimura -- Poetry and the Reformed tradition / James K.A. Smith -- Reformed resources for thinking about fashion / Robert S. Covolo -- Streets of shalom : Reformed reflections on urban design / Eric O. Jacobsen -- Engaging the pluralist campus : Reformed resources / Bethany L. Jenkins -- A Reformed understanding of scholarship / Nicholas Wolterstorff -- Critical race theory, campus culture, and the Reformed tradition / Jeff Liou -- A migrant at the Lord's Table : a Reformed theology of home / Alberto La Rosa Rojas -- Public trauma and public prayer : Reformed reflections on intercession / John D. Witvliet -- Sexism, racism, and the practice of baptism in South Africa : a Reformed and transformative perspective / Nico Koopman -- Confession : practice for civil public discourse / Kyle David Bennett -- Piety and public life : the public imitation of Christ / Jessica Joustra.